SMART CITIES: definition, characteristics, operation, impatcs, challlenges and benefits - Araújo, Liriane Soares; Soares de Moraes, Jessika Thamarys; Barboza De Moraes, Pâmela Cristina (Revista Interface Tecnológica, 2023)
With the constant growth of the population and its migration from rural areas to urban centers, it becomes necessary to develop plans and studies, which aim to meet the diverse needs of society, from resources related to health, education, mobility, housing, security, jobs and all the essential factors in the survival of human beings. In this context, a subject that is growing in academia are smart cities, also known as smart cities in English, which aim to offer technological solutions that can meet different urban structures in their needs. Considering this context, this work aims to present the concepts, characteristics, functioning, impacts, challenges and benefits of smart cities in order to better understand the topic with the aim of contributing to the literature and improving the quality of life of citizens. if technology allows positive and beneficial results. The research methodology used involves descriptive and explanatory bibliographic and documentary analysis of a qualitative approach of an applied nature, as well as an exploratory study on the internet aiming to survey cases in which cities already implement and describe this concept.